ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI NOSTRIL BREATHING DAN AROMATERAPI LAVENDER TERHADAP PENURUNAN TEKANAN DARAH DAN NYERI PADA PASIEN HIPERTENSI DI RSPAD GATOT SOEBROTO - Nurul Aliyyah Rahmah (2023)
Patients with hypertension usually complain of morning headaches, nosebleeds, stiff neck, irregular heart rhythm, blurred vision, ringing in the ears, fatigue, anxiety and confusion, restlessness, nausea and vomiting, throbbing muscles, and chest pain. . Sympathetic activation can increase due to the effects of the pain, which increases the workload of the heart and exacerbates the symptoms of hypertensive patients so that vital signs including blood pressure become unstable. Complementary therapy applied in this study is nostril breathing and the use of lavender aromatherapy. This scientific work aims to analyze the effectiveness of nostril breathing therapy and the use of lavender aromatherapy to reduce blood pressure and pain in hypertensive patients at Gatot Soebroto Army Hospital. After intervention for three days once per day within 15 minutes the acute pain nursing problem was resolved with the result criteria that blood pressure decreased in managed patients and resume patients. Keywords: nostril breathing, aromatheraphy lavender, hypertension,